Bentuk Pertunjukan Tambua Tansa dalam Mengiringi Takbiran di Nagari Maninjau Kabupaten Agam Sumatera Barat - Berliana Nurlita Santi; Murniati Murniati; Yusnelli Yusnelli (SENDRATASIK UNP, 2024)
Tambua Tansa is a beating instrument originating from Minangkabau, a traditional music performance that combines two musical instruments Gandang Tambua and Gandang Tansa performed on a raft or rakik. Rakik is the name for a boat made from an arrangement of bamboo pieces that are decorated as beautifully as possible using Led lights or torches. The purpose of this study was to investigate the form of Tambua Tansa performance in accompanying Takbiran in Nagari Maninjau, West Sumatra Regency. The method used in this study is to use qualitative methods using a descriptive analysis approach. The theories used in this study are structure theory and form theory. The results of this study found that the form of Tambua Tansa performance is the unique processing of Tambua Tansa motifs and rhythms which are played with changing tempos and dynamics, played in groups on rafts or rakik with takbir shouts that illustrate the spirit and enthusiasm of the Maninjau community in welcoming the night of Takbiran.